Comparison of the effectiveness of frontline chemoimmunotherapy regimens for follicular lymphoma used in the United States. Issue 5 (May 2015) - Nastoupil, Loretta J.; Sinha, Rajni; Byrtek, Michelle; Ziemiecki, Ryan; Taylor, Michael; Friedberg, Jonathan W.; Koff, Jean L.; Link, Brian K.; Cerhan, James R.; Dawson, Keith L.; Flowers, Christopher R.
Abstract To compare the effectiveness of frontline rituximab-chemotherapy regimens in clinical practice, we examined outcomes for patients with low-grade, stage III/IV follicular lymphoma receiving rituximab (R) with cyclophosphamide, doxorubicin, vincristine and prednisone (R-CHOP), R with cyclophosphamide, vincristine and prednisone (R-CVP) or R with a fludarabine-based regimen (R-Flu) as frontline therapy. In total, 611 patients meeting these criteria were identified in the National LymphoCare Study: 47% receiving R-CHOP (n = 287), 31% receiving R-CVP (n = 187) and 22% receiving R-Flu (n = 137). Overall response rates were high (R-CVP 87%, R-CHOP 93%, R-Flu 94%; p = 0.017). Median follow-up was 7.4 years. R-CVP was associated with lower 5-year overall survival (R-CVP 76%, R-CHOP 86%, R-Flu 86%; p = 0.021) and progression-free survival (R-CVP 49%, R-CHOP 58%, R-Flu 64%; p = 0.029). There were no significant differences in survival in Cox models adjusted for baseline clinical factors, practice region/setting and post-treatment R maintenance/observation.